role playing method, learning in Penerapan Model Role Playing Untuk Meningkatkan Minat Belajar Pada Pembelajaran IPS Siswa Kelas VII SMP Negeri 1 Batanghari - Lucky Suciati Lucky; Khotijah; Bagus Aziz Saputra; Atik Purwasih; Anita Lisdiana; Wardani (Jurnal Penelitian dan Pendidikan IPS, 2022)
The Role Playing method is a method that allows for active interaction between teachers and students, or between students and other students who interact with each other. This study identified several problems, namely the low student interest in social studies subjects, such as learning that was less interesting so that students lost interest, and the lack of student involvement in learning. Based on these problems, the purpose of this research is to find out the activities of teachers and students in Social Studies learning by applying the Role Playing model in Class VII-4 SMP Negeri 1 Batanghari, as well as to find out the students' learning interest in Social Studies learning by applying the Role Playing model in Class VII -4 SMP Negeri 1 Batanghari. This study used the Classroom Action Research (PTK) method with 32 students from class VII-4 at SMP Negeri 1 Batanghari as subjects. Data collection is done through observation, and data analysis using the percentage formula. The results showed that teacher activity increased from 70.8% in cycle I to 96.9% in cycle II. Meanwhile, student activity increased from 73.9% in cycle I to 93.7% in cycle II. Students' interest in learning also increased from 2.53% in cycle I to 3.11% in cycle II. Thus, the application of the Role Playing model is able to increase student learning interest in social studies learning.